Management of the Oral Health of Children During the COVID-19 Pandemic in Poland - Olszewska, Aneta; Paszynska, Elzbieta; Roszak, Magdalena; Czajka-Jakubowska, Agata (Frontiers in Public Health, 2021)
Managing the oral health of children during the time of a health emergency linked to the current COVID-19 pandemic presents specific problems. A high number of non-specific effective infection control protocols are available in dental settings. It is of fundamental importance to implement specific protocols relating to those clinical situations that normally do not represent an emergency but which now fall into that category. The aim of this study was the comparison of data obtained from the Regional National Health Fund (NFZ) relating to the number and the type of procedures in the oral health management of children aged 0–18 years from the Wielkopolska region, with the months of March and April of 2019 being compared with those of the, respective, pandemic period of 2020. The results showed statistical differences in the number of performed procedures when comparing 2019 and 2020; especially in April (n = 53,077 in 2019 but only n = 2,287 in 2020), when lockdown restrictions reached their highest level and when only 30% of the dental clinics for children were open for patients in the Wielkopolska region of Poland. Regarding surgical cases, there were no differences in percentage frequency between April 2019 and 2020 in terms of extractions. However, an increase was observed in abscess incisions (3.5–17.8%) and surgical dressings (1.5–10.07%). There was a decrease in the total number of performed conservative dentistry procedures in April 2020, but temporary fillings in primary and permanent teeth showed a prominent increase: from 6.4% in 2019 to 19.3% in 2020; and 5.8–11.4%, respectively. Pulp treatment and mucosal lesions therapy fall into the dental emergency category during this COVID-19 pandemic. These cases have shown an increase from 3.2% in 2019 to 12.8% in 2020 for pulp treatment, and from 2.3 to 4.3% for the treatment of oral mucosal lesions. As suspected, after the lockdown was implemented, the number of pediatric dental cases were low. Moreover, the analysis revealed differences in the profile of clinical situations that represented the emergency cases and the pandemic treatment protocols. Future implications suggest that dental prophylactic procedures be included in pandemic protocols with even dental services being limited to a form of urgent treatment. New approaches and treatment models should be implemented in the control of the infectious spread of the disease in the management of the oral health of children in this pandemic period.